REALITAS KEMANUSIAAN DALAM RUBRIK SOSOK HARIAN KOMPAS (ANALISIS WACANA TEUN A. VAN DIJK) (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2020)
The purpose of this study was to determine the reality of humanity that was presented by Kompas Daily in the rubric of the Figure. This study used a qualitative type with a text discourse analysis model of the Teun A. van Dijk model. The subjects of this study were three feature profile posts in the rubric of Figure, each entitled "Maestro Long Song" (Saturday edition, March 2, 2019), "Charity of Facial Reconstruction Sciences" (Saturday edition, March 9, 2019), and "Pocket Money for Poor Children ”(Saturday edition, March 23, 2019). The results showed that in the rubric of the Figure in Kompas Daily, the figures of Mak Itam, Myrtha Artaria, and Reky Martha Groendal which are told in the three feature writings give a representation of how the reality of humanity is presented in a news text. The purpose of this study was to determine the reality of humanity that was presented by Kompas Daily in the rubric of the Figure. This study used a qualitative type with a text discourse analysis model of the Teun A. van Dijk model. The subjects of this study were three feature profile posts in the rubric of Figure, each entitled "Maestro Long Song" (Saturday edition, March 2, 2019), "Charity of Facial Reconstruction Sciences" (Saturday edition, March 9, 2019), and "Pocket Money for Poor Children ”(Saturday edition, March 23, 2019). The results showed that in the rubric of the Figure in Kompas Daily, the figures of Mak Itam, Myrtha Artaria, and Reky Martha Groendal which are told in the three feature writings give a representation of how the reality of humanity is presented in a news text.